2018
DOI: 10.1016/j.burns.2018.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Genital burns in the United States: Disproportionate prevalence in the pediatric population

Abstract: a b s t r a c tIntroduction and objectives: To describe the epidemiology of genital burns in the U.S. and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Most of our cases were burned through hot water and associated with cooking. Our findings were similar to an earlier study of the USA extracting data from the "Electronic Injury Surveillance System Database" from 2000-2016 [162]. Another study conducted in Ghana reported that most pediatric burns were caused by open-fire cooking utilizing wood, manure, garbage, etc.…”
Section: Discussionsupporting
confidence: 90%
“…Most of our cases were burned through hot water and associated with cooking. Our findings were similar to an earlier study of the USA extracting data from the "Electronic Injury Surveillance System Database" from 2000-2016 [162]. Another study conducted in Ghana reported that most pediatric burns were caused by open-fire cooking utilizing wood, manure, garbage, etc.…”
Section: Discussionsupporting
confidence: 90%
“…Burns to the genitalia and perineum should raise significant concerns regarding the cause as they are strongly linked to NAI 13. Scalds are the most common cause of burns to genitalia, especially in younger children and often present in combination with more widespread burn injuries.…”
Section: Assessmentmentioning
confidence: 99%
“…Scalds are the most common cause of burns to genitalia, especially in younger children and often present in combination with more widespread burn injuries. They may require earlier surgical input from plastic surgery and urology 13…”
Section: Assessmentmentioning
confidence: 99%
“…Angel et al reported an incidence of only 3.8% for isolated genital burns in their study (Angel et al, 2002). Due to its sensitive location, genital burns lead to minimal refer to health care practitioners or hospital admissions seeking treatment (Michielsen & Lafaire, 2010) (Tresh et al, 2018).…”
mentioning
confidence: 91%
“…Most burns occur at home. Significant predictors of hospitalization are multi-organ burns, scalding and thermal burns (Tresh et al, 2018).…”
mentioning
confidence: 99%